Front Matter - HLRC Editors (Laureate Education Inc, 2017)
Higher Learning Research Communications (HLRC; ISSN: 2157-6254 [Online]) is published by Laureate Education, Inc. Written communication to HLRC should be addressed to the office of the editor in chief at Laureate Education, Inc., 650 S. Exeter Street, Baltimore, MD 21202, USA. HLRC is designed for open access and online distribution through www.hlrcjournal.com. The views and statements expressed in this journal do not necessarily reflect the views of Laureate Education, Inc. or any of its affiliates (collectively "Laureate"). Laureate does not warrant the accuracy, reliability, currency, or completeness of those views or statements and does not accept any legal liability arising from any reliance on the views, statements, and subject matter of the journal. Acknowledgements The editors gratefully acknowledge the substantial contribution of this issue's peer reviewers.